COVID-19 pandemic and economic impacts in Arab countries: Challenges and policies - Mehdi Abid; Zouheyr Gheraia; Hanane Abdelli; Habib Sekrafi; Alassane Diaw (Research in Globalization, 2022)
The economy of Arab countries faces an extremely difficult and complex year 2020. The crisis caused by the shock of the Covid-19 alters the production system by a double shock of supply and demand, it is crucial to draw up a first detailed assessment of the ramifications of this crisis, which would make it possible to better pose the challenges of the economic policy for future years, faced with a seemingly heavy economic record. This paper studies the impact of COVID-19 on the economy of Arab countries and more particularly on financial markets in terms of financial fragility as well as commercial services and the monetary and banking sector in terms of worsening poverty. It offers a series of recommendations in the short term to address the critical phase of the crisis and in the long term to make the economy of Arab countries more resilient. Such suggestions consist chiefly in: (i) central banks and Arab monetary institutions must take serious steps to curb the Corona-virus spread by introducing a package of incentive policies, (ii) the central banks and Arab monetary institutions must adopt expansionary monetary policies by lowering monetary interest rates. In this way, the international community must work to strengthen the synergy of efforts and to take joint measures and policies to reduce the Corona-virus consequences.
Keywords: 330; COVID-19; Arab countries; Socio-economic